2010
DOI: 10.1042/bj20100122
|View full text |Cite
|
Sign up to set email alerts
|

Iron-binding activity of human iron–sulfur cluster assembly protein hIscA1

Abstract: SYNOPSIS A human homologue of the iron-sulfur cluster assembly protein IscA (hIscA1) has been cloned and expressed in Escherichia coli cells. The UV-visible absorption and EPR (electron paramagnetic resonance) measurements reveal that hIscA1 purified from E. coli cells contains a mononuclear iron center and that the iron binding in hIscA1 expressed in E. coli cells can be further modulated by the iron content in the cell growth medium. Additional studies show that purified hIscA1 binds iron with an iron associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 60 publications
7
37
0
Order By: Relevance
“…Based on in vitro studies of E. coli IscA and SufA and human ISCA1, Ding and coworkers have shown that A-type Fe-S cluster biogenesis proteins are competent Fe donors for cluster assembly on the U-type class of primary scaffold proteins (29;32;35-41). The conserved C-terminal CGC cysteines of A-type proteins have been shown to be essential for high affinity binding of Fe(III) which can be specifically mobilized by L-cysteine for in vitro assembly on IscU (29;32;35-37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro studies of E. coli IscA and SufA and human ISCA1, Ding and coworkers have shown that A-type Fe-S cluster biogenesis proteins are competent Fe donors for cluster assembly on the U-type class of primary scaffold proteins (29;32;35-41). The conserved C-terminal CGC cysteines of A-type proteins have been shown to be essential for high affinity binding of Fe(III) which can be specifically mobilized by L-cysteine for in vitro assembly on IscU (29;32;35-37).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the objectives of this study were to prepare and investigate the detailed electronic, magnetic, redox and vibrational properties of iron-bound forms of Azotobacter vinelandii ( Av ) Nif IscA, as a precursor to understanding the role of Nif IscA in Nif-specific Fe-S cluster biogenesis. Thus far spectroscopic characterization of Fe-bound forms of A-type Fe-S cluster biogenesis proteins have been limited to UV-visible absorption and EPR studies of ferric-bound E. coli IscA and SufA and human ISCA1 (29;32;35). In this work, the spectroscopic and redox properties of both the Fe(III)- and Fe(II)-bound forms of Av Nif IscA have been investigated by the combination of UV-visible absorption, CD and VTMCD, EPR, resonance Raman and Mössbauer spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…The NIF and SUF systems possess many homologous proteins and domains for the IscS, IscU and IscA families. The iron donor protein(s) for the NIF and SUF pathways remains uncertain, although an iron donor role for IscA-type proteins has been suggested [16-18]. Certain classes of bacteria contain both the ISC and SUF operons, with SUF associated with harsh cellular environments, such as oxidative stress or limited iron availability, while the ISC operon appears most relevant for cells functioning under normal conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…The second hypothesis states that IscA and SufA are the alternative scaffold/carrier proteins that bind transient iron-sulfur clusters and transfer the assembled clusters to target proteins [15–22]. However, unlike other proposed iron-sulfur cluster assembly scaffold proteins such as IscU [23], purified E. coli IscA [2428] and human IscA [29] have a strong iron binding activity with an iron association constant of 1.0 × 10 19 M −1 in the presence of the thioredoxin/thioredoxin reductase system under aerobic conditions. Furthermore, the iron center in IscA can be readily mobilized by L-cysteine [30] and transferred for the iron-sulfur cluster assembly in a proposed scaffold IscU in vitro [27], suggesting that IscA/SufA may also act as iron chaperones to recruit intracellular iron [28] and deliver the iron for the iron-sulfur cluster assembly in proteins [27].…”
Section: Introductionmentioning
confidence: 99%